Pengaruh Talent Management, Soft Competency Terhadap Kinerja Karyawan: Studi Kasus Bank Sumsel Babel - Tri Aini; Endah Dewi Purnamasari; Shafiera Lazuarni (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to analyze Talent Management and Soft Competency on Employee Performance at Bank Sumsel Babel. Samples were selected using a saturated sample technique. Data from 38 respondents was collected through a questionnaire. This study implements the multiple linear regression method to analyze the data The results of the investigation show that the partial test for the Talent Management variable has a significant effect on Employee Performance, while the Soft Competency variable has no effect and is not significant on Employee Performance. And to simultaneously test the Talent Management and Soft Competency variables have a significant effect on employee performance. This empirical evidence can provide benefits for companies. To improve employee performance, in the future the company can optimize Talent Management and Soft Competency factors.